1992
DOI: 10.1152/jappl.1992.73.3.887
|View full text |Cite
|
Sign up to set email alerts
|

Breathing patterns during varied activities

Abstract: The level of ventilation attained and breathing patterns adopted during activity have important implications for the distribution and deposition of particles that are inhaled. However, breathing patterns and levels of ventilation adopted during specific physical activities are unknown. We used a noninvasive means of measuring ventilation in subjects performing a variety of activities (bicycling, arm ergometry, lifting, and pulling) during unencumbered (no mouthpiece) breathing and while breathing through a mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 0 publications
3
25
1
Order By: Relevance
“…Conventional recording methods (requiring a mouthpiece and noseclip) used for ventilatory measurement in human subjects are known to alter the ventilation [1][2][3][4]. The present study confirmed the previous findings that breathing through the mouthpiece and occluding the nose changed the breathing pattern.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Conventional recording methods (requiring a mouthpiece and noseclip) used for ventilatory measurement in human subjects are known to alter the ventilation [1][2][3][4]. The present study confirmed the previous findings that breathing through the mouthpiece and occluding the nose changed the breathing pattern.…”
Section: Discussionsupporting
confidence: 89%
“…It is known that in healthy subjects breathing through a mouthpiece results in an increase of tidal volume (VT) [1][2][3], of inspiratory (t I) [2,3] and expiratory time (t E) [2], and inspiratory drive (VT/t I) [2,4]. These changes in ventilation have been attributed to: 1) the influence of the additional dead space; 2) stimulation of the nasal and oral mucosa by the noseclip and mouthpiece; 3) shift of respiratory route from unrestricted nose to mouth.…”
mentioning
confidence: 99%
“…Initially, the use of mouthpiece and nose clip are known to alter the depth and rate of breathing [37], although this effect seems to be restricted to lower levels of ventilation [38]. The present data, therefore, should be used with caution when the ventilatory variables are recorded using a mask or canopy.…”
Section: Study Limitationsmentioning
confidence: 72%
“…Breathing on a mouthpiece tends to alter respiratory patterns, with larger V T and minute ventilation than during unencumbered breathing (Paek and McCool 1992). It is possible that mouthpiece breathing induced greater increases in V T and minute ventilation in the subjects with asthma than in healthy subjects, and that this contributed to the observed increase in UFP deposition.…”
Section: Number Dfmentioning
confidence: 99%